Economic analysis of certain legal solutions in the Draft Mediation Act - Mojašević Aleksandar (Zbornik Radova Pravnog Fakulteta u Nišu, 2014)
The Mediation Act has been applied in the Republic of Serbia since 2005. In the past period, the application of this Act has pointed out to a number of drawbacks and deficiencies in the system of resolving disputes through mediation. The dominant features of the current mediation system are some inadequate legal solutions, poor organization and insufficient preparation of the courts to internalize mediation, failure to provide relevant information about mediation to litigants and other participants in the judicial process, insufficient judicial training and education of lawyers and parties on mediation and other ADR methods, etc. Considering that the primary purpose of mediation is to diminish the litigation caseload and reduce the costs of court proceedings, the basic goal of introducing mediation into the Serbian legal system has not been accomplished. In order to improve the mediation system, the Serbian authorities launched a public debate in 2010 on designing a new legislative act which would eliminate the shortcomings of previous act and improve the efficiency of mediation. After nearly four years, the extensive debate and confrontation of different mediation concepts led to adopting a new Draft Mediation Act in 2013. As compared to the applicable 2005 Mediation Act, the Draft Mediation Act contains some innovations, such as the enforceability of a mediation agreement under specific conditions and the opportunity of introducing mandatory mediation in some cases. In this paper, the author analyzes the above issues on the basis of findings of economic theory and the results of the empirical study on the efficiency of mediation in Serbia in civil matters. In this context, the author argues that the achievement of the above objectives (to reduce the caseload and legal costs] calls for establishing a sustainable mediation system. In addition to instituting good legal solutions (such as mandatory mediation], the system should be supported by joint efforts and financial resources of responsible institutions and individuals. In a nutshell, mediation may come to life only if the legislative efforts are accompanied by a large-scale social action aimed at promoting this form of dispute resolution.